Production of mushroom protein hydrolysates by enzymatic hydrolysis and their physicochemical properties - Banjongsinsiri, Panida; Pasakawee, Krittalak; Noojuy, Nowwapan; Taksima, Takunrat; Rodsuwan, Ubonphan (Food and Applied Bioscience Journal, 2017)
The selected mushrooms (Oyster mushroom, Abalone mushroom and Shiitake mushroom) were hydrolysed with papain enzyme at 50๐ C for the different time (6, 12, 18 and 24 hours) to get the mushroom protein hydrolysates (Oyster mushroom, OMPH; Abalone mushroom, AMPH; Shiitake mushroom, SHMPH), respectively. The result showed that degree of hydrolysis (%DH), total soluble solids (%TSS), sodium chloride (%NaCl), %nitrogen, %protein and free amino acid content of all mushroom protein hydrolysates (MPHs) increased whereas pH value decreased with the increasing extraction time. The optimum MPHs production related with the suitable hydrolysis time and %DH. The hydrolysis timing to produce the highest %DH of OMPH, AMPH and SHMPH (46.54, 38.15 and 25.75) with papain were 18, 18 and 24 hours and provide the highest total amino acid content (mg/100 ml) at 384, 157 and 110, respectively. Based on this result, there is a possibility that Oyster mushroom, Abalone mushroom and Shiitake mushroom can be produced the vegetable protein extracts using the enzymatic hydrolysis process and rendering the useful ingredient for further food and nutraceutical applications.